Ahmadiyah, conflicts, and violence in contemporary Indonesia - Nina Mariani (Indonesian Journal of Islam and Muslim Societies, 2013)
This article examines conflicts and violence experienced by Ahmadiyah commu-nity in Indonesia after reformasi era. In spite of diversities among Muslims inIndonesia, Ahmadiyah (Jemaat Ahmadiyah Indonesia) has been experiencing someforms of violence both from other Muslims and government. The number ofviolence has risen dramatically after the issuing second fatwa from Majelis UlamaIndonesia in 2005 and the Joint Ministerial Decree (SKB) on Ahmadiyah. Thoseforms of violence are issuing decree on banning Ahmadiyah, sealing the mosquesand banning of doing religious activities, and mobbing the mosques and houses,including killing. Furthermore, this paper argues that Indonesia’s goverment doesnot take its responsibility to protect its people particularly from minorities groups,even some local governments also do violence towards Ahmadiyah community.Artikel  ini  membahas  konflik  dan  kekerasan  yang  dialami  oleh  komunitasAhmadiyah di Indonesia setelah masa reformasi. Walaupun Muslim di Indonesiasangat beragam, Jemaat Ahmadiyah Indonesia mengalami beberapa bentukkekerasn baik dari Muslim yang lain maupun dari pemerintah. Jumlah kekerasnayang menimpa mereka meningkat tajam setelah dikeluarkannya fatwa sesat keduadari MUI pada tahun 2005 dan Surat Keputusan Bersama (SKB) tiga menteri mengenai Ahmadiyah. Berbagai bentuk kekerasan yang menimpa mereka yaitupengeluaran peraturan pelarangan keberadaan Jemaat Ahmadiyah di berbagaiprovinsi, penyegelan masjid dan pelarangan melakukan aktifitas keagamaan,penyerangan  masjid-  masjid  dan  rumah-rumah  warga  Ahmadiyah,  bahkanpembunuhan.  Selain  itu,  pemerintah  pusat  sepertinya  tidak  melaksanakankewajibannya untuk melindungi warganya, terutama dari kalangan minoritasbahkan beberapa pemerintah lokal justru melakukan kekerasan terhadap wargaAhmadiyah di daerahnya.